100 rules for living to 100 : an optimist's guide to a happy life - Van Dyke, Dick; McThenia, Tal (Grand Central, 2025)
"On the eve of his 100th birthday, national treasure Dick Van Dyke brings us this autobiographical collection of life advice, stories, and reflections on how he's maintained a zest for life. Dick Van Dyke danced his way into our hearts with iconic roles in Mary Poppins, Chitty Chitty Bang Bang, and The Dick Van Dyke Show. Now, as he's about to turn 100 years old, Dick is still dancing and approaching life with the twinkle in his eye that we've come to know and love. In 100 Rules for Living to 100, he reveals his secrets for maintaining your joie de vivre and making the most out of the life you've been given. Through stories of his pivotal childhood, moments on film sets, his expansive family, and finding love late in life, Dick reflects on both the joyful times and the challenges that shaped him. His indefatigable spirit and positive attitude will surely inspire readers to count the blessings in their own lives, persevere through the hard times, and appreciate the beauty and complexity of being human"--